Understanding the adolescent - Lutchman, Bernard N.
This paper describes some of the characteristics of adolescence: 1) Rapid development, both physically and mentally, which may result in instability and maladjustment; 2) Development of an intensely emotional life; 3) The awakening of sex-consciousness and a keener awareness of beauty; and 4) Craving for creative activity and growth in muscular skills
Keywords: Adolescence